On the variations in the mean convective mixed-layer depth over West Africa - Oluwagbemiga O Jegede (Meteorologische Zeitschrift, 1994)
Using the well-known method of Holzworth (1964) which is based on finding the intersections of upper-air soundings with the dry-adiabat of maximum surface temperatures to estimate the convective mixed-layer depth (MLD), we have obtained in this study representative values of this parameter from an 11-year monthly mean tropospheric data compiled for the West African sub-region. The mean MLD shows recognizable seasonal and spatial variations which is in conformity with the synoptic-scale circulation conditions over the study area. The annual variation indicates a bimodal distribution with the maximum depth of about 1500 m in February (or April for the areas north of 12°N) and in November. The lowest depth of about 650 m is found during the month of August which coincides with the peak of the monsoon season in West Africa. A quantitative relationship for the annual variation of the MLD is also obtained. The MLD values realised are then discussed in relation to the air pollution potential of the West African area.